Dose‐finding results in an adaptive, seamless, randomized trial of once‐weekly dulaglutide combined with metformin in type 2 diabetes patients (AWARD‐5). Issue 8 (22nd May 2014) - Skrivanek, Z.; Gaydos, B. L.; Chien, J. Y.; Geiger, M. J.; Heathman, M. A.; Berry, S.; Anderson, J. H.; Forst, T.; Milicevic, Z.; Berry, D.
<x xml:space="preserve">Abstract</x> Aims AWARD‐5 was an adaptive, seamless, double‐blind study comparing dulaglutide, a once‐weekly glucagon‐like peptide‐1 (GLP‐1) receptor agonist, with placebo at 26 weeks and sitagliptin up to 104 weeks. The study also included a dose‐finding portion whose results are presented here. Methods Type 2 diabetes (T2D) patients on metformin were randomized 3 : 1 : 1 to seven dulaglutide doses, sitagliptin (100 mg), or placebo. A Bayesian algorithm was used for randomization and dose selection. Patients were adaptively randomized to dulaglutide doses using available data on the basis of a clinical utility index (CUI) of glycosylated haemoglobin A1c (HbA1c) versus sitagliptin at 52 weeks and weight, pulse rate (PR) and diastolic blood pressure (DBP) versus placebo at 26 weeks. The algorithm randomly assigned patients until two doses were selected. Results Dulaglutide 1.5 mg was determined to be the optimal dose. Dulaglutide 0.75 mg met criteria for the second dose. Dulaglutide 1.5 mg showed the greatest Bayesian mean change from baseline (95% credible interval) in HbA1c versus sitagliptin at 52 weeks −0.63 (−0.98 to −0.20)%. Dulaglutide 2.0 mg showed the greatest placebo‐adjusted mean change in weight [−1.99 (−2.88 to −1.20) kg] and in PR [0.78 (‐2.10 to 3.80) bpm]. Dulaglutide 1.5 mg showed the greatest placebo‐adjusted mean change in DBP [−0.62 (−3.40 to 2.30) mmHg]. Conclusions The Bayesian algorithm allowed for an efficient exploration of a large number of doses and selected dulaglutide doses of 1.5 and 0.75 mg for further investigation in this trial.